2018
DOI: 10.3345/kjp.2018.61.4.132
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal duplication revealed by posterior reversible encephalopathy syndrome

Abstract: We report a unique case of intestinal duplication detected on posterior reversible encephalopathy syndrome (PRES) in a 13-year-old girl. She was admitted to the pediatric Emergency Department because of generalized seizures. Radiological assessment revealed a large, well-defined, thick-walled cystic lesion in the mid abdomen, suggestive of duplication cyst associated to a PRES. Exploration confirmed the diagnosis of ileal duplication cyst, and the mass was resected. The postoperative course was uneventful. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this research, we found that while the pathology leading up to the procedure, the therapy, and the sedation used during the procedure were hypothesized to be in relation to the onset of PRES, in fact there does not seem to be a direct correlation with one pathology versus another. We have identified cases of postoperative PRES in patients treated for gastrointestinal pathology [27,30,47], gynecologic pathology [12], and even urologic pathology [31,48]. Several anesthesiologic reports [12,27,31,50] on PRES have argued that the major causative factor could be suboptimal pressure control in hypertensive patients [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In this research, we found that while the pathology leading up to the procedure, the therapy, and the sedation used during the procedure were hypothesized to be in relation to the onset of PRES, in fact there does not seem to be a direct correlation with one pathology versus another. We have identified cases of postoperative PRES in patients treated for gastrointestinal pathology [27,30,47], gynecologic pathology [12], and even urologic pathology [31,48]. Several anesthesiologic reports [12,27,31,50] on PRES have argued that the major causative factor could be suboptimal pressure control in hypertensive patients [25,26].…”
Section: Discussionmentioning
confidence: 99%